Whole genome characterization, recombination, variation, satellites and phylogeny analyses of Tomato leaf curl Palampur virus infecting courgetti squash (Cucurbita pepo L.) in Iraq - Mohammed, Mohammed S.; Lahuf, Adnan A. (Journal of Kerbala for Agricultural Sciences, 2023)
Durning season of 2021-2022, symptoms of leaf curl, yellowing, crumpling and stunting were observed commonly on courgetti crop in Al-Yusufiyah region, Baghdad Province, Iraq. Diseased courgetti leaves were collected randomly and sent for sequencing with Illumina MiSeq. Pairwise nucleotide analysis of the assembled contigs revealed the maximum identity of 98-99% and 95-99% with Tomato leaf curl Palampur virus (ToLCPalV) for DNA-A and DNA-B components, respectively. The DNA-A component (OQ693629.1) contains six main genes encoding six proteins, while DNA-B component (OQ693630.1) comprises only two genes encoding two proteins, with the presence of non-coding regions between genes in both the two segments. Furthermore, the recombination breakpoint analysis shows that ToLCPalV Baghdad-1/Iraq segment DNA-A (OQ693629.1) and ToLCPalV isolate Mosul segment A (OR052249.1) are the parent of the recombinant isolates: ToLCPalV isolate Kufa segment DNA-A (OP810506.1) and ToLCPalV segment A (ON254271.1) from Karbala. However, the ToLCPalV Baghdad-1/Iraq segment DNA-B (OQ693630.1) with ToLCPalV segment DNA-B (OP620406.1) from Kufa are the parent of ToLCPalV isolate Babylon1 segment DNA-B (ON229620.1). As well as, there was no evidence discovered for the association of alpha- and/or beta-satellites with ToLCPalV infecting courgetti crop. Single nucleotide polymorphisms (SNP) analysis indicates a common genetic variation within the current isolate under study and the other Iraqi isolates. Phylogenetic analysis confirms the genetic relationship between the genomics components of Iraqi ToLCPalV and various international isolates of the same virus, especially those distributed in Saudi Arabia and Iran that could be a possible the origin and introduction of ToLCPalV into Iraq.